Peran Diklat Koding dan Kecerdasan Artifisial (KKA) dalam Pengembangan Kompetensi Guru di Era Transformasi Pendidikan Kotamobagu - Kusnadi Pobela; Susetyo rini; M. Syaifuddin; Yus M. Cholily (Universitas Sarjanawiyata Tamansiswa, 2026)
The development of digital technology requires teachers to develop new competencies in utilizing technology-based learning tools. This situation makes improving teacher capacity through relevant training, such as the Coding and Artificial Intelligence (KKA) Training, an urgent need to support the digital transformation of education. This study aims to describe the implementation and impact of KKA Training on improving teacher competency. The study used a qualitative descriptive method with data collection techniques including questionnaires, interviews, observation, and documentation. The research informants were teachers participating in the KKA Training in Kotamobagu City. Data analysis was conducted using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that KKA Training is highly urgent in preparing teachers for the changing paradigm of technology-based learning. This program improves teachers' knowledge and skills in coding and AI, strengthens pedagogical abilities, and fosters a positive mindset in utilizing technology. Furthermore, KKA Training also strengthens the integration of TPACK (Teaching, Assessment, and Assessment) so that teachers are better prepared to develop adaptive and innovative learning. The study concludes that KKA Training is a strategic instrument in improving teacher competency and accelerating the digital transformation of education